Comparative Lingustics and Edvard Lotko's research - Balowski, Mieczysław (Bohemica Olomucensia, 2018)
In the first part of the article, author describes three stages of comparative research conducted in Poland: confrontation of phonetic, phonological, inflectional and word formation system of all Slavic languages, confrontation of selected levels of two or more Slavic languages and development of literary languages on the Czech-Polish borderland. The author starts with a description of historical and comparative-historical linguistics. Then he proceeds to typological research in a characterological variant. He indicates the creation of mixed codes on the Czech-Polish border. In the second part, the author characterizes the scientific works of Professor Edvard Lotka, placing them on the background of previously described schools of linguistics.
Keywords: comparative linguistics; Slavic languages; language at Czech and Polish borderland; mixed codes; language system; Edvard Lotko